Hubungan Antara Perilaku Asertif dan Insecure attachment dengan Dating Violance pada Remaja - Nanda Putri Marthawijaya; Rr. Dwi Astuti (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Dating violence is a form of deviant behavior that is prevalent among adolescents. This study aims to examine the relationship between assertive behavior and insecure attachment with dating violence in adolescents. This research uses a quantitative method with a correlational approach. The study sample consisted of 150 adolescents aged 18-23 years who are currently or have experienced dating violence. Data collection was conducted using Likert-based psychological scales, namely the Conflict in Adolescent Dating Relationship Inventory (CADRI) to measure dating violence, the Assertive Behavior Inventory (ABI) for assertive behavior, and the Wissink et al. (2016) model for insecure attachment. Data analysis was performed using multiple linear regression with SPSS 26.0. The results showed no significant relationship between assertive behavior and dating violence (p = 0.006) or between insecure attachment and dating violence (p = 0.163). This indicates that other factors, such as parenting styles, trust in relationships, and family conflicts, may have a more significant influence on dating violence. Further research is recommended to explore additional contributing factors and develop more effective prevention strategies.